Improving elementary students’ interest and achievement in civic education through jigsaw cooperative learning (IAIN Kendari, 2026)
Civics Education in elementary schools requires participatory learning that enables students to understand civic values, discuss social issues, and develop responsible attitudes toward globalization. This study aimed to describe the implementation of the Jigsaw cooperative learning model and analyze its effect on students’ learning interest and Civics achievement. A classroom action research design was conducted in two cycles involving 28 sixth-grade students at SD Negeri 2 Pulosaren. Data were collected through classroom observation, a learning interest questionnaire, achievement tests, and reflection notes. The findings showed that Jigsaw gradually transformed teacher-centered instruction into collaborative learning through home groups, expert groups, peer explanation, and reflective instructional refinement. Students’ learning interest increased from 54.3% in the pre-cycle to 71.4% in Cycle I and 89.3% in Cycle II. Classical mastery also improved from 46.4% to 71.4% and reached 89.3%. These results indicate that structured peer teaching, positive interdependence, and role clarity can strengthen students’ participation, motivation, and conceptual understanding in elementary Civics learning. Keywords: classroom action research; Civics Education; elementary school; Jigsaw cooperative learning; learning achievement; learning interest